DETERMINATION OF COBALT(II) AND NICKEL(II) WITH ISOAMYLXANTHATE AS A COMPLEXING REAGENT IN MICELLAR MEDIA - Shar, G. A.; Soomro, G. A. (The Nucleus, 2020)
Cobalt(II) and nickel(II) were determined spectrophtometrically using sodium isoamylxanthate as a complexing reagent in aqueous phase in the presence of anionic surfactant sodium dodecylsulphate (SDS). Beer’s law was obeyed for Co(II) and Ni(II) over the concentration range 3.0-35 and 2.0-37 Î¼gmL-1 respectively. The Î»max, molar absorptivity and Sandell’s sensitivity of Co(II) and Ni(II) were 360 nm and 416 nm; Îµ is 0.19 and 0.2 (Ã— 104 mol-1cm-1) 31.1 and 29.3 ng cm-2 respectively. Maximum absorbance at 1:2 (M: L) molar ratio suggested the formation of M(C6H11OS2)2 where M = Co(II) and Ni(II). The complex remained stable for more than 2 h. The optimized reagent concentration 0.5 % was used throughout the study. Surfactant concentration of 1.0 % SDS caused significant enhancement in absorbance. Maximum absorption was observed at 360 nm and 416 nm for Co and Ni complexes, respectively. The absorption maxima were obtained at optimized pH of 7.0. Validation of method has been made by comparing the results with Atomic Absorption Spectrometry; no significant difference was obtained between the two methods at 95 % confidence interval. The method is simple, accurate, economical and has been applied to the determination of cobalt(II) and nickel(II) in industrial wastewater, pharmaceutical and edible oil samples.